Post-Growth Geographies : Spatial Relations of Diverse and Alternative Economies - Lange, Bastian; Hülz, Martina; Schmid, Benedikt; Schulz, Christian (2021)
Post-Growth Geographies examines the spatial relations of diverse and alternative economies between growth-oriented institutions and multiple socio-ecological crises. The book brings together conceptual and empirical contributions from geography and its neighbouring disciplines and offers different perspectives on the possibilities, demands and critiques of post-growth transformation. Through case studies and interviews, the contributions combine voices from activism, civil society, planning and politics with current theoretical debates on socio-ecological transformation.